Konsep Pendidikan Islam Integral Menurut Muhammad Natsir - Fauzi, Hairul (LoroNG: Media Pengkajian Sosial Budaya, 2012)
One of the challenges of Islamic education today is the dichotomy of science, between the sciences (‘ulum al-dunya) with the religious sciences (‘ulum al-syar’i). Indonesian Muslim intellectuals who tried to formulate Islamic education in accordance with haparan religion, nation and State, namely Muhammad Natsir. Focus problem in this research is how Muhammad Natsir Thinking about Islamic Education, How Integral Thought Muhammad Natsir. Thought Muhammad Natsir about Integral Islamic education is the education model that combine general education and religious education, sustainability is evidenced by not polarize between west and east. To implement the Islamic education curriculum Integral Muhammad Natsir used is the national curriculum and religious curriculum. The concept of Integral Muhammad Natsir Islamic education is the idea for the renewal of Islamic Religious Education, which now more and more the secularists to separate religion from life. Salah satu tantangan pendidikan Islam saat ini adalah dikotomi ilmu, yakni ilmu-ilmu alam (‘ulum al-dunya) dengan ilmu-ilmu agama (‘ulum al-syar’i). Salah satu intelektual Muslim Indonesia yang mencoba merumuskan pendidikan Islam sesuai dengan haparan, bangsa agama dan Negara, ialah Muhammad Natsir. Fokus masalah dalam penelitian ini adalah bagaimana pemikiran Muhammad Natsir tentang Pendidikan Islam, dan pendidikan Islam Integral. Pemikiran Muhammad Natsir tentang pendidikan Islam Integral adalah model pendidikan yang menggabungkan pendidikan umum dan pendidikan agama. Keberlanjutan ini dibuktikan dengan tidak mempolarisasi antara barat dan timur. Untuk menerapkan kurikulum pendidikan Islam Integral, Muhammad Natsir menggunakan kurikulum nasional dan kurikulum agama. Konsep Muhammad Natsir tentang pendidikan Islam Integral adalah gagasan dalam pembaharuan Pendidikan Agama Islam, yang sekarang lebih condong sekuler, memisahkan agama dari kehidupan.